Pengaruh Kualitas Pelayanan, Ketepatan Waktu, Dan Kepercayaan Layanan J&T Express Terhadap Kepuasan Konsumen Berbelanja Di Marketplace (Studi Kasus Pada Mahasiswa FEB Unisma) - Melisari Melisari; Eka Farida; Restu Millaningtyas (UNIVERSITAS ISLAM MALANG, 2022)
AbstractIn the current digitalization era, various types of online shopping or marketplaces as well as support for providing delivery service facilities from internet-based transportation services, have changed people's behavior from shopping traditionally to shopping online. The popularity of online shopping in the community in recent years has driven the growth of the logistics sector in the country, marked by an increase in the use of delivery services.The purpose of this study was to describe consumer satisfaction, service quality, timeliness, and trustworthiness of J&T Express shopping services on the Marketplace, to determine and analyze the effect of service quality, timeliness, and trustworthiness of J&T Express services on consumer satisfaction shopping at the Marketplace, to find out and analyze the effect of service quality on J&T Express services on consumer satisfaction shopping at the Marketplace. to find out and analyze the effect of timeliness on J&T Express services on consumer satisfaction shopping at the Marketplace, to find out and analyze the effect of trust in J&T Express services on consumer satisfaction shopping at Marketplace.The results showed that service quality, timeliness, and trustworthiness of J&T Express services had a significant effect on consumer satisfaction shopping at Marketplace, service quality on J&T Express services had a significant effect on consumer satisfaction shopping at Marketplace, timeliness on J&T Express services had no significant effect on satisfaction. consumers shop at Marketplace, trust in J&T Express services has a significant effect on consumer satisfaction shopping at Marketplace. Regarding timeliness on the statement